Understanding Nazi ideology: the genesis and impact of a political faith - Müller Frøland, Carl (McFarland & Company, Inc., Publishers, 2020)
"Nazism did not arise in a vacuum but was deeply rooted in German culture. From German Romanticism sprang ideas of great significance for the genesis of the Third Reich-notions of the individual as a part of the national collective, and of history as a ceaseless struggle between opposing forces. Tracing the origins of the Nazi "political religion," this book examines its foundation in ultra-nationalism, totalitarianism, the Führer cult, racial theory and anti-Semitism, and the glorification of violence-all swathed in an element of occultism-and its culmination in the global cataclysm of World War II and the Holocaust."--